Generators's cryopoetics - Tošović, Branko (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The subject of research are literary works that are automatically produced by generators as a basic instrument of artificial intelligence for professional, utilitarian, experimental, ludic, entertainment, stylistic, (auto)presentation, demonstration, etc. purposes.. Cryopoetics is a part of poetics that deals with the artistic conception, presentation, structuring and expression of cold as (a) an important motif and component of a literary work, (b) a natural phenomenon, somatic and mental state, individual and social marking. The central category of this discipline is cryolism – a system of static and dynamic phenomena related to cold as an objective given (the state of living and inanimate objects), a procedural given (action, state, event, event, fable, etc.) and a relational given (relationships). The paper examines literary texts whose author is artificial intelligence, and whose basic motif is cryolism. Through the analysis of specific examples, this research aims to answer the question (a) to what extent artificial intelligence is able to generate quality literary texts, (b) to what extent and in what ways does the poetics of natural cryolism (the one whose author is a living writer or poet) differ from the poetics of artificial cryolism (the one whose author is artificial intelligence).